Behind the Scenes : Experience Managing and Conducting Large Impact Evaluations in Colombia - Briceño, Bertha; Cuesta, Laura; Attanasio, Orazio (Taylor and Francis, 2013)
As more resources are being allocated to impact evaluation of development programmes, the need to map out the utilisation and influence of evaluations has been increasingly highlighted. This paper aims at filling this gap by describing and discussing experiences from four large impact evaluations in Colombia on case- study basis. On the basis of learning from our prior experience in both managing and conducting impact evaluations, desk review of available documentation from the monitoring and evaluation system, and structured interviews with government actors, evaluators and programme managers, we benchmark each evaluation against 11 standards of quality. From this benchmarking exercise, we derive five key lessons for conducting high-quality and influential impact evaluations: investing in preparation of good terms of reference and identification of evaluation questions; choosing the best methodological approach to address the evaluation questions; adopting mechanisms to ensure evaluation quality; laying out the incentives for involved parties in order to foster evaluation buy-in; and carrying out a plan for quality dissemination.